THE USE OF THE FLOANDDAY TIKTOK CHANNEL IN PRONUNCIATION - Disa Pertami; Chusnul Chotimah; Tauricha Astiyanda (Lingua, 2023)
This research is entitled The Use of Floandday TikTok Channel in Pronunciation. Based on the problem that often occurs in students is the influence of the mother tongue which is still used in English. So, the pronunciation in English is still not good and correct. As a result, there are often misunderstandings in speaking. With advances in technology at this time there is a social media that is very popular with students or teenagers, namely TikTok. TikTok is not only for watching dance videos but also for educational media. One of the English education accounts on TikTok is Floandday. Using a qualitative descriptive method, the purpose of this study is to provide more information about the use of TikTok Floandday accounts in learning pronunciation for students. This research was conducted for 6 months with observation and interview instruments on 10 students aged 15-17 years on followers on the Floandday TikTok account. The results of this study are positive responses from students on Floandday accounts who can easily learn English according to phonetics without feeling bored or being judged wrongly in the English learning process.